SOCIAL NETWORK INFLUENCES ON SELF-CARE AND HEALTH AMONG OLDER ADULTS WITH MULTIPLE CHRONIC CONDITIONS. (11th November 2018) - LeBlanc, R; Jacelon, C; Chiodo, L; Paik, A; Aulino, F
Abstract: Background: Older adults are the fastest growing segment of the population in the United States. and manage multiple chronic conditions. Self-care behaviors are a priority to effectively manage chronic conditions, yet a gap exists in our understanding of how social networks influence the outcomes of self-care behavior and health within the context of aging and managing multiple chronic conditions. Objective: The aim of this study was to determine how social network features and functions influence self-care behaviors and health among community dwelling older adults with multiple chronic conditions. Design: This study integrated an explanatory sequential mixed methods design. Methods: A cross-sectional sample of eighty-nine community dwelling older adults participated. Descriptive statistics were used to describe social networks. Bi-variate correlations and multiple regression statistics were used to examine the relationships of social networks with the dependent variables of self-care behaviors and health. Qualities that emphasize the contexts expanded the analysis of the survey data. and social support. Results: Ties strength and social support predicted the outcome of therapeutic self-care and mental health. Distinctions between tangible support and psycho-social support are made. Thematic analysis expanded understanding on network size, psycho-social support, activation of support and interaction frequency and type. Conclusions: Social networks influence self-care behaviors and mental health. In aging and living with multiple chronic conditions, this research proposes new ways to understand social members in creating supportive self-care networks and understanding how self-care support is activated and social relationship influences in older age.